Optimizing Persistent Memory Transactions - Zardoshti, Pantea; Zhou, Tingzhe; Liu, Yujie; Spear, Michael (Proceedings / International Conference on Parallel Architectures and Compilation Techniques, 2019)
Byte-addressable, non-volatile, random access memory (NVM) has the potential to dramatically accelerate the performance of storage-intensive workloads. For applications with irregular data access patterns, and applications that rely on ad-hoc data structures, the most promising model for interacting with NVM is a transactional model. However, the specifics of the model matter significantly. We introduce two models for programming persistent transactions. We show how to build concurrent persistent transactional memory from traditional software transactional memories. We then introduce general and model-specific optimizations that can substantially improve the performance of persistent transactions. Our evaluation shows a substantial improvement in the both the latency and scalability of persistent transactions.